1999
DOI: 10.2307/1387762
|View full text |Cite
|
Sign up to set email alerts
|

Age and Religiosity: Evidence from a Three-Wave Panel Analysis

Abstract: Using pooled time series with random and fixed effects regression models, we examine the effect of age, period, and family life course events on a measure of religious influence on daily life in a panel of 1,339 adults interviewed three times between 1980 and 1992. The results showv a significant, non-linear increase in religiosity with age, with the greatest increase occurring between ages 18 and 30. We also found a significant decline in religiosity between 1980 and 1988, but no evidence of a period effect b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
166
1
9

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(192 citation statements)
references
References 22 publications
16
166
1
9
Order By: Relevance
“…Some research in the US indicates that young adults' religiosity increases with age. Argue et al (1999) report that religiosity increases faster in the age interval 18-30. Stolzenberg et al (1995) found that family formation events have a significant effect for the increase of church membership by age 32.…”
Section: Interpreting Associations Between Religion and Fertilitymentioning
confidence: 99%
“…Some research in the US indicates that young adults' religiosity increases with age. Argue et al (1999) report that religiosity increases faster in the age interval 18-30. Stolzenberg et al (1995) found that family formation events have a significant effect for the increase of church membership by age 32.…”
Section: Interpreting Associations Between Religion and Fertilitymentioning
confidence: 99%
“…It has been well documented in the literature that religiosity increases with age (Argue et al 1999;Campbell and Curtis 1994). In regard to immigrants, this age pattern consists of two components: duration of residence in the country of origin ('age at migration') and duration of residence in the country of destination ('duration').…”
Section: Journal Of Ethnic and Migration Studies 761mentioning
confidence: 99%
“…Studies of religion have noted that as people stage of development, their association with both recognised religious societies and their own particular beliefs change (Argue, Johnson, and White 1999;Ingersoll-Dayton, Krause, & Morgan 2002;Wilson & Sherkat 1994). Religiosity is a complex concept and difficult to define (Holdcroft 2006).…”
Section: Literature and Proposed Model Developmentmentioning
confidence: 99%